1978
DOI: 10.1128/iai.19.2.613-620.1978
|View full text |Cite
|
Sign up to set email alerts
|

Granuloma formation by synthetic bacterial cell wall fragment: muramyl dipeptide

Abstract: A synthetic muramyl dipeptide, N-acetylmuramyl-L-alanyl-D-isoglutamine, which possesses the same structure as that of a part of the peptidoglycan monomer of wax D of tubercle bacilli or bacterial cell walls was found to induce, when injected in water-in-oil emulsion, massive granulomas often accompanying abscesses in the site of injection and draining lymph nodes of guinea pigs and rats. The granulomas were composed mainly of epithelioid cells 2 weeks after injection and were indistinguishable from those induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
23
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
5
23
0
Order By: Relevance
“…This suggests that MDP may increase the viability of macrophages. However, the possibility that MDP might stimulate macrophage proliferation rather than viability could also be raised to explain the slight reduction in the number of attached, living macrophages, because MDP has been reported to stimulate macrophages to release macrophage growth factor (14), and many macrophages showing cell division were seen in the granuloma evoked by MDP (4). Thymidine uptake into the trichloroacetic acid-insoluble fraction of macrophages, however, was found not to be enhanced but to be suppressed by MDP.…”
Section: Effect Of Mdp On 3h-thymidine Uptake By Macrophagesmentioning
confidence: 99%
“…This suggests that MDP may increase the viability of macrophages. However, the possibility that MDP might stimulate macrophage proliferation rather than viability could also be raised to explain the slight reduction in the number of attached, living macrophages, because MDP has been reported to stimulate macrophages to release macrophage growth factor (14), and many macrophages showing cell division were seen in the granuloma evoked by MDP (4). Thymidine uptake into the trichloroacetic acid-insoluble fraction of macrophages, however, was found not to be enhanced but to be suppressed by MDP.…”
Section: Effect Of Mdp On 3h-thymidine Uptake By Macrophagesmentioning
confidence: 99%
“…A muramyl dipeptide (MDP), N-acetylmuramyl-L-alanyl-n-isoglutamine, in bacterial cell walls is an essential structure for their diverse biological activities including an immunoregulatory capacity (3). We and other investigators have found, with different parameters, that MDP activates macrophages (6,7,II,14,18,19,20,21). We suggested further that the activation of macrophages by MDP as assayed by macrophage migration inhibition does not require lymphocyte participation (9,24).…”
mentioning
confidence: 99%
“…In parallel with these findings, a variety of biological activities of MDP have been observed and shown to depend on the same specific structure (6,31,34). In vivo, MDP has been reported to possess pyrogenicity (16), stimulatory effect on the reticuloendothelial system (35), granulomatogenicity in several animals (10,32) and arthritogenicity in the rat (22). To further study the mechanism of such in vivo effects of MDP, a target cell for MDP has been searched for and different types of immune cells including macrophages and T-and B-cells have been implicated (11,22,29,34,38).…”
mentioning
confidence: 87%